Platelet Membrane-Coated HGF-PLGA Nanoparticles Promote Therapeutic Angiogenesis and Tissue Perfusion Recovery in Ischemic Hindlimbs - Wang, Peng; Di, Xiao; Li, Fengshi; Rong, Zhihua; Lian, Wenzhuo; Li, Zongshu; Chen, Tianqi; Wang, Wenjing; Zhong, Qing; Sun, Guoqiang; Ni, Leng; Liu, ChangWei (ACS applied bio materials, 2025)
Therapeutic angiogenesis has garnered significant attention as a potential treatment strategy for lower limb ischemic diseases. Although hepatocyte growth factor (HGF) has been identified as a key promoter of therapeutic angiogenesis, its clinical application is limited due to its short half-life. In this study, we successfully developed and characterized platelet membrane-coated HGF-poly(lactic-co-glycolic acid) (PLGA) nanoparticles (NPs). These nanoparticles demonstrated enhanced capabilities to promote endothelial cell (EC) proliferation, migration, and tube formation in vitro. Additionally, their efficacy in improving tissue perfusion and promoting angiogenesis was confirmed in a hindlimb ischemia rat model. Our findings suggest that platelet membrane-coated HGF-PLGA-NPs could serve as a promising therapeutic approach for enhancing angiogenesis and restoring tissue perfusion in ischemic conditions.